India in the Indo-Pacific Understanding India's security orientation towards Southeast and East Asia - Malhotra, Aditi (International and Security Studies, 2022)
Angesichts der sich verändernden Weltordnung nehmen Schwellenländer zunehmend Einfluss auf die gegenwärtige Dynamik regionaler Sicherheiten. Die Autorin beschreibt, wie sich die sicherheitspolitische Rolle Indiens im indo-pazifischen Raum in den letzten zwei Jahrzehnten weiterentwickelt und ausgeweitet hat. Es zeigt sich, dass zwischen der politischen Rhetorik Neu-Delhis und dem politischen Handeln vor Ort eine deutliche Kluft besteht. Die Gründe für diese Ineffektivität werden in dem Buch weiter untersucht. In view of the fast-changing world order, emerging countries are increasingly influencing the dynamics of regional securities. This timely and in-depth book examines India's reorienting strategic posture and describes how New Delhi's security policy in the Indo-Pacific region has evolved and expanded over the past two decades. The author argues that India's quest to leverage its geostrategic location to emerge as an Indo-Pacific actor faces multiple challenges, which create a clear divide between the country's political rhetoric and action on the ground. The author critically examines these contradictions to better situate India's security role in an increasingly fluid Indo-Pacific region